The Relationship of Arm Muscle Strength and Strength Force with Mash Results Spring in the Volleyball Game for Male Students - Musdalifah, Nyimas; Kristina, Putri Cicilia; Rizhardi, Rury (PPSDP International Journal of Education, 2024)
This study aims to determine the relationship between arm muscle strength and muscle flexibility with semi-smash results in volleyball games in class X male students of SMA Negeri 1 Indralaya. This type of research is correlation research. The population used was male students in class X SMA Negeri 1 Indralaya. The sample for this research consisted of 70 male students. This research method uses method correlation. The data collection technique in this research used a test. The instruments used were the pull-up test, sit-and-reach test, and semi-smash test. The results of statistical analysis from multiple correlation analysis obtained an F-count of 68.63, then consulting the F-table with a significance level of 5%, obtained an F-table of 3.14. The magnitude of the double correlation (R) obtained is R= 0.82, and the coefficient of determination (R2) obtained is 0.672, meaning (0.672 x100%) = 67.2% of the semi-smash results are determined by a combination of arm muscle strength and stick flexibility. Based on the results of this research, it can be concluded that there is a significant relationship between arm muscle strength and muscle flexibility with semi-smash results in volleyball games for male students in class X of SMA Negeri 1 Indralaya.